2020
DOI: 10.1039/c9an01289c
|View full text |Cite
|
Sign up to set email alerts
|

Raman mapping of fentanyl transdermal delivery systems with off-label modifications

Abstract: Raman mapping and chemometric models were used to characterize crystal formation in fentanyl transdermal delivery systems resulting from off-label modifications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 56 publications
1
3
0
Order By: Relevance
“…The examination of the patch surface using an SEM excluded the presence of the TST ( Figure 5 ), which suggested the location of the crystals in the deeper layers of the matrix and proves that the re-crystallization of TST occurred not on the air/patch contact surface but in deeper layers of the polymeric matrix. The observation leads to the conclusion that re-crystallization was not initiated by external conditions (e.g., contact with air or mechanical stress) as previously observed for fentanyl patches [ 24 ]. One cannot rule out that the observed phenomena for TST in the acrylate patches indicate that the dissolved fraction is present in the concentration close to the saturated state, which should result in high thermodynamic activity and thus an optimal release rate [ 13 ].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The examination of the patch surface using an SEM excluded the presence of the TST ( Figure 5 ), which suggested the location of the crystals in the deeper layers of the matrix and proves that the re-crystallization of TST occurred not on the air/patch contact surface but in deeper layers of the polymeric matrix. The observation leads to the conclusion that re-crystallization was not initiated by external conditions (e.g., contact with air or mechanical stress) as previously observed for fentanyl patches [ 24 ]. One cannot rule out that the observed phenomena for TST in the acrylate patches indicate that the dissolved fraction is present in the concentration close to the saturated state, which should result in high thermodynamic activity and thus an optimal release rate [ 13 ].…”
Section: Discussionsupporting
confidence: 72%
“…A comparative analysis of the SEM micrographs with optical images allowed to obtain additional information on the location of the crystalline API. Only in the case of A2 with CYT, a considerable number of drug particles was located superficially, whereas the TST crystals present in A1 and A2 were not observed using the SEM (Figure 5) [24]. The detailed study of the microstructure of the adhesive patches continued using a SEM, where the area of interest was the patch surface.…”
Section: Optical Microscopy the Sem And Raman Mappingmentioning
confidence: 99%
“…104 A depth profile of nicotine penetration into the SC after patch application indicated that nicotine transport was nearly steadystate after the patch was applied for 2 h. Raman mapping was also used to characterize unwanted fentanyl structural and chemical changes when the adhesive delivery system was improperly used. 105 For topical drugs that localize in the skin, RS has been utilized to characterize the bioavailability within the targeted area. Zarmpi et al employed confocal Raman imaging to identify the strongly Raman-active model skin penetrant 4cyanolphenol (CP) at least 10−40 μm into the skin, below the SC.…”
Section: Delivery In Cells and Tissuesmentioning
confidence: 99%
“…Raman imaging has been implemented for direct, quantitative mapping of drug compounds in topical formulations and their delivery into the skin and appendages. For example, drug delivery and absorption events were interrogated at the interface between porcine skin and (trans)­dermal formulations . A depth profile of nicotine penetration into the SC after patch application indicated that nicotine transport was nearly steady-state after the patch was applied for 2 h. Raman mapping was also used to characterize unwanted fentanyl structural and chemical changes when the adhesive delivery system was improperly used . For topical drugs that localize in the skin, RS has been utilized to characterize the bioavailability within the targeted area.…”
Section: Imaging Drug Molecule Distribution and Delivery In Cells And...mentioning
confidence: 99%